Transitioning to Minimal Footwear: a Systematic Review of Methods and Future Clinical Recommendations - Warne, Joe P. (Sports Med Open, 2017)
BACKGROUND: Recent interest in barefoot running has led to the development of minimalist running shoes that are popular in distance runners. A careful transition to these shoes has been suggested and examined in the literature. However, no guidelines based on systematic evidence have been presented. The purpose of this review is to systematically examine the methods employed in the literature to transition to minimal footwear (MFW), as well as the outcomes to these studies in distance runners. In addition, MFW transition guidelines for future clinical practice will be presented based on observations from this review. METHODS: A systematic database search was employed using PubMed online as the primary database. Twenty papers were included in the final review. RESULTS: All studies implemented a prospective transition design to MFW with a detail of this transition provided, which increased MFW exposure up to an average of 60% (30–100%) at completion. Only 8/20 studies included injury prevention exercises, and 9/20 included gait retraining. The main outcomes of this transition included limited positive evidence of transitioning into MFW for running economy (n = 4 studies) and muscle development (n = 5). The injury incidence comparing running during the MFW transition (17.9 injuries per 100 participants) to matched participants in conventional running shoes (13.4 injuries per 100) appears equivocal (p = 0.219; effect size phi (φ) = 0.06 [very small]). Finally, several important recommendations for clinical practice and future research have been presented. CONCLUSIONS: It is hoped that this paper will present important first steps in unifying the process of transitioning to MFW, both for academic and clinical use.